Train Related Injuries: Growing Concern in Developing Countries and Five-year Experience at Level-1 Trauma Center in India. Issue Volume 34:Issue s1(2019) (May 2019) - Bagaria, Dinesh; Banerjee, Niladri; Ud, Parvez Mohi; Gupta, Amit; Joshi, Mohit; Sagar, Sushma
Abstract : Introduction: Indian railway systems are fourth largest in the world, and cause on average 15 deaths daily due to various intentional and unintentional reasons. This study presents a 5-year retrospective data analysis of polytrauma patients with train-related injuries. Aim: To highlight key lessons learned from data analysis to inform better safety measures and laws. Methods: Trauma registry data between 2012 and 2016 were analyzed for patients with train-related injuries. Data from 726 patients were analyzed for demographics, event, injuries, management, and final outcome. ISS was used to quantify the extent of injury. Results: Mean patient age was 33 years with an 86% to 14% male to female ratio. 62% of patients were in the 20- to 40-year age group. Average time of arrival at health facility post-injury was 3.3 hours. Half of the patients were trespassers. Mean ISS was 11.65. Chest injuries were present in 24.6% of patients, with half requiring interventions like ICD insertion or surgery. 20% of patients underwent amputations of extremities. 40% of patients needed admission to the ICU. 3.5% died in the Emergency Department (ED). Mean hospital stay was 17 days with an in-hospital mortality of 17.4%. Discussion: This analysis is the largest to date showing comprehensive injury patterns and outcomes of train-related injuries from a developing country. Patients injured on the platform and off the platform had the same severity of injuries. This analysis shows the need for safety measures and strict law enforcement both at the station and at the track.